Actions of salbutamol, disodium cromoglycate, and placebo administered as aerosols in acute asthma. Issue 9 (September 1981) - Hasham, F; Kennedy, J D; Jones, R S
Abstract : The effects on the peak expiratory flow rate of the drug sequences, placebo-salbutamol-disodium cromoglycate and placebo-disodium cromoglycate-salbutamol administered via a nebuliser were examined in 35 children with asthma. Twenty children were each examined once within 4 hours of admission to hospital with an acute attack of asthma, and the remaining 15 children were examined later in the attack on two occasions. The placebo effect of sterile water accounted for about half of the total bronchodilator action both early and late in the attack. It is suggested that this effect is due to the action of water on the surface film of surfactant, causing collapse of bubbles and strands or webs of mucoid material, thus decreasing airways resistance. At this time salbutamol is significantly more potent than disodium cromoglycate as a bronchodilator agent.